Protocols to co-culture human primary lung cells in the simple-flow device - Cinta Iriondo; Sem Koornneef; Kari-Pekka Skarp; Marjon Buscop-van Kempen; Anne Boerema-de Munck; Robbert J. Rottier (STAR Protocols)
Summary: Human lung models replicate various aspects to address diverse research questions. The complexity of human lung models, such as co-cultures and lung-on-chip devices, is increasing, but details on culture methodologies are often lacking. Here, we describe steps for the isolation, maintenance, and co-culturing of primary epithelial, endothelial, and mesenchymal cells derived from human lung resection material. We then detail procedures for 3D printing the simple-flow device, setting it up with co-cultures of human primary epithelial and endothelial cells under fluidic conditions. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.